Historiografi Hadis: Studi Pemikiran Rasyid Aylal dalam Kitab Shahih Al-Bukhari Nihayah Usturah - Sherina Wijayanti; Muhammad (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2023)
Abstract This research discusses Rasyid Aylal???s criticism of Imam Bukhari and this book Sahih Al-Bukhari , as well as the responses of other scholars to Aylal???s criticism. Aylal???s criticism is written in the book Sahih Al-Bukhari Nihayah Usturah, published in 2018. The presentation of Aylal???s criticism, which is written with invalid references, has sparked controversy among scholars, especially considering Aylal???s identity as a non-hadith scholar, rasing questions about the quality of his critique of hadith literature. It is undeniable that Imam Bukhari is known as a monumental hadith scholar, and his book is recognition is rejected by Aylal. Aylal argues that Imam Bukhari is a liar, and his book, which contains many weak hadiths, should not be considered a sahih (authentic) book. This research was conducted using the library research method with a literature review approach, where the literature sources were taken from various classical books and journals related to the topic. This research results in three main findings: First, Rasyid Aylal is known as a controversial figure in critiquing the historicity of the book Sahih Al-Bukhari. Second, Aylal???s thingking is based on hadiths found in Sahih Al-Bukhari that are often considered irrational, and there is no evidence that the companions truly collected written hadiths. Third, Aylal???s accusations in book Sahih Al-Bukhari Nihayah Usturah are not subtantiated and contain various form of plagiarism